ANALYZING A TEXTBOOK “BRIGHT AN ENGLISH COURSE FOR JUNIOR HIGH SCHOOL” PUBLISHED BY ERLANGGA PUBLISHING COMPANY - hastri firharmawan (Journal of English Language Learning, 2020)
Textbook is an essential component in teaching and learning process. It facilitates teachers to deliver the teaching-learning materials and helps students in order to learn more easily. However, not all textbooks used in schools are good and appropriate. The aim of this study is to analyze the compatibility of the materials in the textbook used by the second graders of MTs Ma’arif Nahdlatul Ulama 03 Kemranjen Banyumas with basic competencies in the 2013 curriculum. The type of this research was document content analysis. Data is in the form of words, phrases, or sentences which are English materials in the textbook “Bright an English Course for Junior High School Students” published by Erlangga Publisher in 2013. The result of this research shows that this textbook belongs to be a good textbook. The textbook is supportive to learning since the materials provided within the textbook are compatible with the basic competencies required by 2013 English curriculum for Junior High School. All basic competencies (KD) are evenly distributed in the textbook with the following percentage composition: basic competency 3 gains 50% and basic competency 4 gains 50%. It means that the textbook is suggestible to be used in teaching.Key words: textbook; basic competency; analysis